PENGARUH PEMBERIAN BUBUK DAUN PEPAYA CALIFORNIA (CARICA PAPAYA) TERHADAP MORTALITAS JENTIK NYAMUK - Mariani, Rina; Nurlinawati, Nurlinawati (Scientific Of Environmental Health and Diseases, 2021)
ABSTRACT Introduce : Diseases that transmitted by mosquitoes have a high risk of mortality and morbidity. The effort to reduce the risk of diseases that transmitted by mosquitoes is by giving larvaside in powder form. Papaya leaves (Carica Papaya) are plants that have the potential for mosquito larvae mortality. Methods: Quantitative research, a type of pre-experimental research with Intac Group Comparasion research design. The research instrument used observation sheets. Purposive sampling was taken with a total of 50 samples grouped into 4 treatment groups with a dose of 60 mg, 150 mg, 300 mg, 500 mg and 1 control group. Results: The lowest larval mortality is at a dose of 60 mg (10%) and the highest mortality at a dose of 500 mg (60%). The results of the analysis in the treatment group are 60 mg, 150 mg and 300 mg obtained p-value> 0.05 so in conclusion there were no significant differences between the treatment groups of papaya leaf powder treatment group at that dose with the control group. The 500 mg group has a p-value of 0.011 <0.05, so it can be concluded that there is a significant difference between the papaya leaf powder treatment group with a concentration of 500 mg of the control group. Conclusion: The addition of papaya leaf powder with a concentration of 500 mg has an positive effect on the mortality of mosquito larvae. Keywords: Powder, Papaya Leaves, Mortality ABSTRAK Latar Belakang : Penyakit yang ditransmisikan oleh nyamuk memiliki risiko tinggi pada mortalitas dan morbiditas. Adapun upaya untuk mengurangi risiko penyakit yang ditularkan oleh nyamuk ialah dengan pemberian larvasida dalam bentuk bubuk. Daun pepaya (Carica Papaya) merupakan tanaman yang memiliki potensi sebagai larvasida alami. Metode : Penelitian kuantitatif, jenis penelitian pre-eksperimental dengan desain penelitian Intac Group Comparasion. Instrumen penelitian menggunakan lembar observasi. Pengambilan sampel purposive sampling dengan jumlah 50 sampel yang dikelompokan menjadi 4 kelompok perlakuan dengan dosis 60 mg, 150 mg, 300 mg, 500 mg dan 1 kelompok kontrol. Hasil : Mortalitas jentik terendah pada dosis 60 mg (10%) dan mortalitas tertinggi pada dosis 500 mg (60%). Hasil analisis pada kelompok perlakuan 60 mg, 150 mg dan 300 mg didapatkan nilai p-value > 0,05 sehingga tidak terdapat perbedaan yang signifikan antara kelompok perlakuan bubuk daun pepaya pada dosis tersebut dengan kelompok kontrol. Kelompok 500 mg memiliki nilai p-value 0,011 < 0,05, maka dapat disimpulkan terdapat perbedaan yang signifikan antara kelompok perlakuan bubuk daun pepaya konsentrasi 500 mg dengan kelompok kontrol. Kesimpulan : Pemberian bubuk daun pepaya dengan konsentrasi 500 mg mempunyai pengaruh terhadap mortalitas jentik nyamuk. Kata kunci : Bubuk, Daun Pepaya, Mortalitas